Changes in facial signs due to age and their respective weights on the perception of age, on a tired‐look or a healthy glow among differently aged Chinese men. (29th August 2020) - Flament, F.; Abric, A.; Amar, D.; Ye, C.; Caron, J.; Negre, C.
Abstract: Objective: To determine the respective weights of certain facial signs on the assessment of perceived age, tired‐look and healthy glow on Chinese men of different ages. Material and methods: Photographs were taken of the faces of 420 Chinese men of different ages, under standardized conditions. These photographs allowed to focus and define 15 facial signs, which were then graded by 15 experts and dermatologists, using standardized scales provided by a reference Skin Aging Atlas. The facial signs were dispatched into 5 clusters, namely wrinkles/texture, ptosis/sagging, pigmentation disorders, vascular disorders and cheek skin pores. A naïve panel, composed of 80 Chinese women, of similar age range were asked, when viewing full‐face photographs, to: (i) attribute on a 0–10 scale their perception of both the tired‐look and healthy glow aspects and (ii) estimate the age of the subject. Results: With the exception of vascular disorders, the severity of all 4 clusters increased with age, although at different rates. The ptosis/sagging or pigmentation disorders showed a rather regular progression. Although perceived ages and real ages were found to be closely correlated, the vast majority of subjects were judged older by 2–10 years. The changes in facial signs (and their related clusters) were significantly correlated with perceived age, with the exceptions of skin spot density and cheek skin pores. Although the aspects of tired‐look and healthy glow were logically found to be anti‐correlated, tired‐look was more statistically associated with perceived age for the five clusters. Signs of eye contour appear to be closely correlated with the perception of a tired‐look. Conclusion: Within facial clinical clusters, wrinkles/texture and ptosis/sagging are major factors in the assessment of perceived age in Chinese men. Tired‐look appears to be strongly associated with perceived age. Abstract : PLS regression coefficients of 2‐components PLS model and 95 % confidence intervals based on jack‐knife procedure of perceived ages (PA) with all clinical signs (up) (Q 2 = 0.90 / R 2 = 0.91) and clinical clusters (down) (Q 2 = 0.88 / R 2 = 0.89) in Chinese men, showing the relative weight of each sign or cluster. In grey: no significant impact.. Résumé: Objectif: De déterminer, pour des hommes chinois d'âges différents, les poids respectifs de certains signes faciaux entrant dans l'estimation de la perception des visages pour l'âge, l'air fatigué ou l'éclat. Matériel et Méthodes: Les visages de 420 hommes chinois d'âges différents ont été photographiés dans des conditions standardisées. Ces clichés ont permis à 15 experts et dermatologistes d'évaluer 15 signes cliniques selon des échelles éditées dans les références Atlas Cliniques du Vieillissement. Ces signes faciaux sont regroupés dans 5 groupes (rides/texture, ptose/relâchement, désordres pigmentaires, désordres vasculaires, pores de la joue). Un panel de 80 consommatrices chinoises, d'un âge comparable, a été recruté pour donner leurs perceptions sur chaque visage complet photographié: d'abord en attribuant sur une échelle de 0 à 10 un score pour leurs perceptions de l'air fatigué et de l'aspect éclatant de santé, puis en estimant l'âge apparent du volontaire. Résultats: A l'exception des Désordres vasculaires, la sévérité des 4 groupes cliniques s'accroit avec l'âge selon des cinétiques différentes, parmi lesquelles la ptose/relâchement ou les désordres pigmentaires montrent la progression la plus constante et linéaire. Malgré une très importante et significative corrélation entre âge apparent et âge réel, une majorité des volontaires ont été jugés plus vieux que leurs âges réels, entre 2 et 10 ans. Les variations des signes faciaux (ou des groupes cliniques associés) ont été montrés significativement corrélées à l'âge apparent, à l'exception de la densité des taches pigmentaires et des pores de la joue. Bien que l'air fatigué et l'éclat sont logiquement observés comme anti‐corrélés, c'est l'air fatigué qui se trouve le plus relié à l'âge apparent sur les 5 groupes cliniques. Les signes du contour des yeux apparaissent comme les plus corrélés à la perception de l'air fatigué. Conclusion: Parmi les groupes cliniques, les rides/texture et la ptose/relâchement sont les facteurs majeurs dans l'attribution d'un âge perçu pour les hommes chinois. L'air fatigué apparaît comme très fortement relié à l'âge apparent.